تعليم المفردات العربية باستخدام الوسيلة السمعية البصرية لطلاب الصف الرابع بالمدرسة الابتدائية الاسلامية سبيل الله جوكير جومبانج - Suci Fitria Rachma; Isniyatun Niswah (Program Studi Pendidikan Bahasa Arab, 2023)
One interesting way among the methods used for learning is the Arabic language learning method using audio-visual media. That is a learning method that is delivered using media in the form of images and sound, such as short films, videos, or songs, illustrated magazines, posters and so on. This study uses qualitative methods with a descriptive approach, and this type of researcher uses case study research, data collection techniques in the form of observation, interviews and documentation, data analysis techniques in the form of data reduction, data presentation and conclusions. The results of this study concluded that students at the Islamic elementary school Sabilillah Cukir Jombang memorized vocabulary or mufrodat faster by the teacher using audio-visual media, namely pictorial and sound media.